Frequency of Pneumonia in Children, Classified as Severe Pneumonia According to IMNCI Standards at Tertiary Care Hospital (Medical Forum Monthly, 2021)
Objective: To determine the frequency of pneumonia in children, classified as severe pneumonia according to IMNCI standards at tertiary care hospital. Study Design: Cross-Sectional Descriptive Study Place and Duration of Study: This study was conducted at the CMC children hospital Larkana from November, 2017to April, 2018. Materials and Methods: In a cross-sectional descriptive study, children between 2 -59 months of age of either sex referred from IMNCI clinic classified as severe Pneumonia were enrolled after informed consent from November 2017 to April 2018 in CMC children hospital Larkana. Interviews using structured questionnaires were used for history of cough and examination for chest in drawing was taken, then Chest X ray done. The data was analyzed by13version SPSS. Results: The mean age of enrolled participants was 16.5±13.3 months. 63 (60.6%) were male and 41 (39.4%) were female. Mean duration of cough was 7.8±4 days and mean duration of chest in drawing was 2.6±1.2 days. A total of 60 (57.7%) patients developed pneumonia. Of 60 patients of pneumonia 41 (68.3%) had infiltrations, 16 (26.7%) had consolidation and 10 (16.7%) had pleural effusion on chest x-rays. Conclusion: It is concluded from this study that the frequency of radiological pneumonia is high in IMNCI classification of pneumonia as reported in the world so reduction of this burden of disease should be a national health priority. Chest X-ray is an important tool in diagnosing severe pneumonia, particularly in situations where other means of investigations are insufficient.